THE RELATIONSHIP OF PARENTS' MOTIVATION AND STUDENT'S LEARNING INTEREST TOWARDS READING ACTIVITIES OF THE QURAN(SMP IT Robbani Sintang Kalimantan Barat) - Yogi Supyana; Arnadi; Jaelani (IJGIE (International Journal of Graduate of Islamic Education), 2021)
This research includes correlational research. This research was carried out at the IT Robbani Sintang Middle School, West Kalimantan in 2021. This study contained three variables, namely two independent variables and one dependent variable. Data collection techniques used in this study were questionnaires and documentation. Based on the results of research on the relationship between parents' motivation and students' interest in learning to read Al-Quran at SMP IT Robbani Sintang, West Kalimantan, it can be concluded as follows: (1) There is a significant relationship between parents' motivation (X1) on reading Al-Quran activities. Qur'an (Y) students of Class VIII SMP IT Robbani Sintang West Kalimantan where the contribution is 39.9%. (2) There is a significant relationship between interest in learning (X2) on the activity of reading the Koran (Y) students of Class VIII SMP IT Robbani Sintang West Kalimantan where the contribution is 46.3% (3) There is a significant relationship between parents' motivation (X1) and interest in learning (X2) together, with the activity of reading the Koran (Y) of Class VIII students of SMP IT Robbani Sintang, West Kalimantan, where the contribution is 30.8%